PERANCANGAN ULANG INTERIOR STASIUN KERETA API PEKALONGAN DENGAN PENDEKTAN BEHAVIOR REDESIGN OF PEKALONGAN RAILWAY STATION INTERIOR WITH BEHAVIOR APPROACH - Agustriani, Marina; Liritantri, Widyanesti; Puspa Nabila, Ganesha (eProceedings of Art & Design, 2024)
This design aims to bring about significant changes to Pekalongan RailwayStation, focusing on the theme "Multi-Functional Space of Heritage" Recognized as anintegral element in the history of Indonesia's railway network, the station holds strategicpotential as a crucial regional transit hub. The applied designmethodology involves indepth analysis of historical station usage, user needs, and train travel trends. The theme "Multi-Functional Space of Heritage" is thoroughly implemented in the interior andexterior design of the station by creating harmony between contemporary design that maintains the authenticity of the existing elements of the building. The design approachused focuses on optimizing spatial planning in the behavior of space users, efficient circulation, and maximum utilization of space functions. The design results show thatthese design changes not only improve the aesthetic aspects of the station, but also have a positive impact on the user experience, space efficiency, and maintaining theauthenticity of the building. This design improves the functionality of the station as a transportation hub, meeting the needs of users while maintaining local values. This designfinding is expected to provide valuable guidance for developers and designers in the development of railway stations in various regions, by paying attention to and combiningheritage values and user behavior needs. As a result, the project is expected to be an inspirational model for the future development of the railway station, which harmoniously blends history and functionality. Keywords: station, heritage, behavior